Change in the social life of urban public spaces: The rise of mobile phones and women, and the decline of aloneness over 30 years. (June 2015) - Hampton, Keith N; Goulet, Lauren Sessions; Albanesius, Garrett
This study illustrates that over the past 30 years, Americans have become less socially isolated while using public spaces. Based on content analysis of films from four public spaces over a 30-year period, the behaviour and characteristics of 143, 593 people were coded. The most dramatic changes in the social life of urban public spaces have been an increase in the proportion of women and a corresponding increase in the tendency for men and women to spend time together in public. Despite the ubiquity of mobile phones, their rate of use in public is relatively small. Mobile phone users appear less often in spaces where there are more groups, and most often in spaces where people might otherwise be walking alone. This suggests that, when framed as a communication tool, mobile phone use is associated with reduced public isolation, although it is associated with an increased likelihood to linger and with time spent lingering in public. We argue that public spaces are an important component of the communication system that provides exposure to diverse messages, brings people into contact to discuss their needs and interests, and helps people recognise their commonalities and accept their differences. The increased tendency to spend time in groups while in public contrasts with evidence from other research that suggests a decline in American public life, and that mobile phones have increased social isolation in public spaces. The increase in group behaviour, women and lingering in public may have positive implications for engagement within the public sphere.